The Case of the Missing Acts of the (Other) Apostles - Legrand, Lucien (Asian Horizons, 2024)
The Antiochian paradox of the New Testament poses the question of why St. Paul, who was dispatched by the capital of Syria, Antioch, travelled westward to the Greco-Roman world and Europe rather than eastward to Syria and Asia. Antioch, the first significant Christian community after Jerusalem, played a role in the establishment of Christianity. The Roman Empire brought about significant changes, but the East was equally important as the West. It is possible that Paul and Barnabas travelled by sea from Antioch to Greece and Rome. Antioch was linked to historical Orient nations such as Babylonia, Media, Persia, and India by critical trading routes. Messianic advent messengers would have received financial, moral, and spiritual support, as well as conduits, from the Jewish communities of the Eastern Diaspora. Paul and Barnabas sailed west to Cyprus, Greece, Rome, and Spain, despite their improved perspectives on the world. Eastern Christianity may have expanded as a result of a unique missionary dynamism that differed from Western Christianity. Christianity expanded in the East in a manner similar to the Jewish Diaspora, with Israel lacking a “Congregation for the Evangelisation of the People” or missionary organisation. The Diaspora's vitality was derived from individual and collective witness, rather than proselytising.